KEPEMIMPINAN, SUMBER DAYA, DAN PARTISIPASI MASYARAKAT: FAKTOR DI BALIK KEBERHASILAN BUMDESA - Sareng, Caecilia Elchyta Dua; Pradana, I Putu Yoga Bumi; Kellen, Pius Bumi (JURNAL TRIAS POLITIKA, 2024)
Abstract:.This study aims to determine the performance of Village-Owned Enterprises' business governance in Puan To'a Village-Owned Enterprises, Tebuk Village and Kimang Buleng Village-Owned Enterprises, Riit Village and the factors that contribute to the performance of Village-Owned Enterprises' governance in Puan To'a Village-Owned Enterprises, Tebuk Village and Kimang Buleng Village-Owned Enterprises, Riit Village. This study uses a qualitative method with a comparative study research type and data collection procedures using interviews, document studies, and observations, with data collection from 22 informants involved in the Village-Owned Enterprises governance process. The results of the study indicate that the performance of governance on the principles of profit, transparency, accountability, and sustainability in Kimang Bulenge Village-Owned Enterprises is not by the principles of good governance where the recruitment of administrators, especially in the election of directors, is not carried out through tests but is directly selected by the village head, the formation of the second management does not have AD/ART, financial reporting is not optimal due to different training and educational backgrounds, and has formed a Village-Owned Enterprise twice but has experienced congestion. The factors behind the differences in performance consist of three dimensions, namely the leadership dimension, the organizational resource dimension, and the external environment dimension. From each existing factor, the Kimang Buleng Village-Owned Enterprise can take steps in its governance performance for the sustainability of the Village-Owned Enterprise. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana kinerja tata kelola bisnis BUMDesa pada BUMDesa Puan To’a Desa Tebuk dan BUMDesa Kimang Buleng Desa Riit serta faktor-faktor yang berontribusi pada bagi kinerja tata kelola BUMDesa Puan To’a Desa Tebuk dan BUMDesa Kimang Buleng Desa Riit. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian studi komparasi dan prosedur pengumpulan data menggunakan wawancara, studi dokumen dan observasi dengan pengumpulan data berasal dari 22 informan yang terlibat dalam proses tata Kelola BUMDesa. Hasil penelitian menunjukkan bahwa kinerja tata kelola pada prinsip profit, transparansi, akuntabilitas dan sustainable pada BUMDesa Kimang Bulenge belum sesuai dengan prinsip tata Kelola yang baik dimana pada perekrutan pengurus khususnya pada pemilihan direktur tidak dilakukan melalui tes tetapi dipilih langsung oleh kepala desa, pembentukan pengurusan kedua tidak memiliki AD/ART, pelaporan keuangan belum maksimal karena pelatihan serta latar belakang pendidikan yang berbeda, dan sudah dua kali membentuk BUMdesa namun harus mengalami kemacetan. Faktor-faktor dibalik perbedaan kinerja, terdiri dari tiga dimensi yaitu dimensi kepemimpinan, dimensi sumber daya organisasi dan dimensi lingkungan eksternal. Dari setiap faktor yang ada bisa diambil oleh BUMDesa Kimang Buleng dalam kinerja tata Kelola demi keberlanjutan BUMDesa.